Business and Environmental Obligations: A Study of The Transitioning Regulatory Framework - Kumari, Priya; Ojha, Pranav Anand; Kakkar, Pranjal (Christ University Law Journal, 2024)
The primary obligation to provide a safe, clean and healthy environment and by extension, a means to tackle climate change lies on the concerned State. The State has the authority to frame policies and legislation to guarantee the same. It has also been witnessed that States have started accepting this responsibility since the historic Stockholm Declaration of 1972. However, environmental degradation and the ill effects of climate change have taken a lethal form. It is primarily due to man-made or human-induced activities that climate change has accelerated. And burdening only the nation-states to take action on a global issue might not yield results. It is with the heightening of this aspect, businesses or the private sector have been looped in through several regulatory mechanisms to take proper action. This was considered appropriate as businesses utilise an economy’s resources and is thus, said to have certain social obligations. Moreover, it is also felt that they have the requisite infrastructure, technology and know-how to support governmental action. India has been at the forefront of fulfilling environmental obligations since the beginning. And has mandated corporate social responsibility in 2013 and recently, the environmental, social and governance mechanisms as well. But when it comes down to witnessing changes in the fulfilment of environmental obligations, India is still facing problems. This paper aims to highlight the connection between business, human rights and the environment, if there is any. This shall be done with a focus on the current regulatory framework for the same in India. Keywords: Business, Climate Change, Environment, Human Rights, Policy